2013
DOI: 10.1038/bjc.2013.113
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and barriers to patient participation in RCTs

Abstract: Background:Recruitment of patients into randomised clinical trials (RCTs) is essential for treatment evaluation. Appreciation of the barriers and drivers towards participation is important for trial design, communication and information provision.Method:As part of an intervention to facilitate effective multidisciplinary team communication about RCTs, cancer patients completed two study-specific questionnaires following trial discussions. One questionnaire examined reasons why patients accepted or declined tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 11 publications
10
75
1
Order By: Relevance
“…In the present study, an overwhelming majority of patients indicated that they would join a drug trial prior to initiation of definitive treatment. These results mirror previously reported clinical cancer trial participation data in which approximately 80 % of cancer patients accept randomization into clinical trials [20]. When probed further, our patient population indicated they would accept trial enrollment in order to Bdo everything possible to fight the cancer^and Bto help others facing this cancer in the future^.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, an overwhelming majority of patients indicated that they would join a drug trial prior to initiation of definitive treatment. These results mirror previously reported clinical cancer trial participation data in which approximately 80 % of cancer patients accept randomization into clinical trials [20]. When probed further, our patient population indicated they would accept trial enrollment in order to Bdo everything possible to fight the cancer^and Bto help others facing this cancer in the future^.…”
Section: Discussionsupporting
confidence: 85%
“…Mean number of working days (± SD) associated with specimen acquisition, pathology review, PIK3CA molecular analysis, and the complete mutational analysis pathway (specimen requisition to PIK3CA result) for the final 15 specimens. Error bars denote one standard deviation patient factors may influence recruitment [20,21]. As part of planning for a pre-clinical drug trial targeting PIK3CA mutations, we felt it was prudent to examine willingness of treatment-naïve patients to accept a novel neoadjuvant therapy in relation to a recent cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the proposed SCC trial, participation in the surgical stage was seen as less of a threat than, for example, taking part in a trial involving a new drug or in a trial in which there was the possibility of being randomised to a placebo arm, which has been recognised as a disincentive to participate in trials. 720,721 Although almost three-quarters of participants claimed they would definitely or probably be willing to be randomised into the first surgical stage, the decision about whether or not to participate may be complicated by potential cosmetic implications, particularly for younger, female, patients and for SCCs located on the face or in a functionally sensitive area (e.g. around the eye).…”
Section: Squamous Cell Skin Cancer Work Programmementioning
confidence: 99%
“…Studies have demonstrated that elderly individuals, those with comorbid conditions, ethnic minorities (including African Americans and Latinos), and those with lower socioeconomic status tend to be underrepresented in cancer clinical trials [5][6][7]. Barriers to enrollment include concern about adverse effects of unstudied therapies, mistrust of research, financial constraints, lack of availability of trials for treatment of a particular condition, or lack of access to trials [8][9][10]. In addition, although randomized trials typically test the interventions that appear most promising based on preliminary efficacy and safety data, patients may be confused by the concept of randomization, they may not like the fact that their doctor will not be directly determining which intervention they receive, or they may be unwilling to risk being assigned to a control arm.…”
Section: Patient Participationmentioning
confidence: 99%